The Interaction of K and O2 on Au(111): Multiple Growth Modes of Potassium Oxide and Their Catalytic Activity for CO Oxidation. Issue 39 (23rd August 2022) - Shi, Rui; Liao, Wenjie; Ramírez, Pedro J.; Orozco, Ivan; Mahapatra, Mausumi; Kang, Jindong; Hunt, Adrian; Waluyo, Iradwikanari; Senanayake, Sanjaya D.; Liu, Ping; Rodriguez, José A.
Abstract: In industrial catalysis, alkali cations are frequently used to promote activity or selectivity. Scanning tunneling microscopy, ambient‐pressure X‐ray photoelectron spectroscopy, and density‐functional calculations were used to study the structure and reactivity of potassium oxides in contact with the Au(111) surface. Three different types of oxides (K2 O2, K2 O and KO y with y <0.5) were observed on top of the gold substrate at 300–525 K. Initially, small aggregates of K2 O2 /K2 O (1–2 nm in size) were seen at the elbows of the herringbone structure. After increasing the K coverage (>0.15 ML), large islands of the oxide (20–40 nm in size) appeared. These islands contained a mixture of K2 O and KO y ( y <0.5). A key correlation was found involving the structure, oxidation state, and chemical activity of the alkali oxide. The small aggregates of potassium oxide had a very high catalytic activity for the oxidation of CO, being much more than plain promoters. Abstract : Three different types of potassium oxides were observed on top of Au(111) at 300–525 K. Small aggregates of K2 O2 /K2 O (1–2 nm in size) were seen at the elbows of the herringbone structure. After increasing the K coverage (>0.15 ML), large islands of the oxide (20–40 nm in size) appeared with a mixture of K2 O and KO y ( y <0.5). A key correlation was found involving the structure, oxidation state, and catalytic activity of the alkali oxide.